Biaxial serial excision: A technique to deal with benign skin lesions and scars - Kalpesh J Gajiwala (Indian Journal of Plastic Surgery)
Background: In the best of hands, the ultimate surgical scar of an otherwise well-performed surgery is unpredictable, and surgical techniques are constantly evolving to prevent or revise large scars. The present series uses the principles of serial excision to reduce the eventual scar length. Materials and Methods: Between January 1991 and December 2010, 30 patients were operated upon. In the first stage, a lesion was reduced in two dimensions with the intent to create a smaller lesion with the long axis favourably placed. The residual lesion was then excised after 4 weeks or more. Results: The resultant scars were smaller and better aligned, with an excellent skin match. Conclusion: A well-planned serial excision in a biaxial manner helps reduce the final scar.